MURDER Learning Model in Digitally Supported Learning: Effects on Reflective Thinking Skills across Learning Creativity Levels - Meriyati Meriyati; Chairul Amriyah; Syaiful Anwar; Robingatin Robingatin; Romlah Romlah; Agus Jatmiko (CV FOUNDAE, 2025)
This study examines the impact of the MURDER learning model on students' reflective thinking skills from the perspective of learning creativity in a digitally supported learning context. The study used a quasi-experimental design with a pretest–posttest control group pattern. The study subjects consisted of 54 prospective early childhood education teacher students at a state university in Lampung Province, selected using a purposive sampling technique. Reflective thinking skills were measured using a written test based on reflective thinking indicators, while learning creativity was measured through a questionnaire and classified into high, medium, and low levels. Data were analyzed using analysis of covariance and further tests to examine the main effects of the learning model, the level of learning creativity, and the interaction between the two. The results showed differences in students' reflective thinking skills based on the learning model and the level of learning creativity. In addition, the relationship between the learning model and reflective thinking skills varied according to the level of student learning creativity. The interaction analysis showed that students with higher levels of learning creativity tended to demonstrate better reflective thinking results in learning conditions using the MURDER model. Thus, the impact of implementing the MURDER learning model on reflective thinking is conditional and depends on the characteristics of student learning creativity.